Spatial-economic and Geopolitical Interests of Russia, The USA and China in Central Asia: Competition, Coincidence of Wants and Strategies in a Changing World - Eroyan, Asya E.; Kolpak, Eugeny P.; Litvinova, Svetlana F.; Gusakov, Nikolay P.; Ryazantsev, Sergey V. (International Review of Management and Marketing, 2016)
Central Asia is potential support being some sort of the global region-donor for restructure and expansion of economy of the Russian Federation, the United States and China. One of the purposes which the Russian Federation constantly pursues is the creation and preservation of unified economic space of the CIS. However, in spite of the fact that trade, economic and social relations of the Russian Federation with the countries of Central Asia have greatly weakened more than in ten years, they are still more structured on their contents than similar ones, for example, of the European countries or the USA. The Central Asian region is rich in natural resources and mineral reserves. There are large volumes of oil, natural gas, gold, cotton production. Central Asia is also a sales market of the Russian equipment and industrial goods and also a source of some resources which Russia comes short of such as food, vegetables, cotton, and so on. The Central Asian region is quite rich in oil resources and natural gas, but earlier the ways of their transportation were under the full control of Russia. Taking advantages of a geographical location and control over capital construction projects, Russia has almost completely monopolized the transportation of energy carriers from Central Asia that provides the great influence on policy of the countries of the region and great economic benefit. Keywords: geopolitics, commodity turnover, resources, world powers JEL Classifications: D72, O13, O32